A comparative study of primary skin and subcutaneous tissue closure and open skin technique in emergency laparotomy for perforative peritonitis: an observational and prospective study - Mukherjee, Ramanuj; Samanta, Sudipta (International Surgery Journal, 2018)
Background: Surgical site infections (SSI) are major complications following laparotomy for perforative peritonitis largely affecting the quality of life, increasing morbidity and mortality. The study conducted seeks the factors that may be associated with post-operative surgical site infection. Methods: A comprehensive observational and prospective study reporting advantages and disadvantages of Primary Closure (PC) and Delayed Primary Closure (DPC) for SSI, duration of hospital stay and morbidity following various aetiologies of perforative peritonitis requiring emergency laparotomy. Results: Incidence of SSI was less in the DPC group (7.4%) compared to the PC group (42.9%) (p= 0.0040. Length of hospital stay was comparable in both groups, mean 13.52 days in the DPC group versus 14.07 days in the PC group (p=0.586). Significantly higher rates of SSI were found in patients with ASA grade >2 (p=0.012). Duration of surgery >4 hours and intra-operative transfusion were also found to have higher rates of SSI, but these differences were not significant (p=0.181 in both cases). Incidence of SSI did not have any co-relation with site of perforation. Conclusions: SSI increases the hospital stay by approximately 5 days average. DPC significantly reduces the incidence of SSI in perforative peritonitis patients but the advantage of DPC over PC is questionable. Patients with ASA grades >2 were found to have significantly higher rates of SSI. Patients with >4hours surgery and patients with intra-operative transfusion also had higher rates of SSI, but this was not significant. Site of perforation have no co-relation with incidence of SSI.